Different Synaptic Plasticity After Physiological and Psychological Stress in the Anterior Insular Cortex in an Observational Fear Mouse Model - Shi, Wenlong; Fu, Yuan; Shi, Tianyao; Zhou, Wenxia (Frontiers in Synaptic Neuroscience, 2022)
Post-traumatic stress disorder (PTSD) can be triggered not only in people who have personally experienced traumatic events but also in those who witness them. Physiological and psychological stress can have different effects on neural activity, but little is known about the underlying mechanisms. There is ample evidence that the Insular Cortex, especially the anterior insular cortex (aIC), is critical to both the sensory and emotional experience of pain. It is therefore worthwhile to explore the effects of direct and indirect stress on the synaptic plasticity of the aIC. Here, we used a mouse model of observational fear to mimic direct suffering (Demonstrator, DM) and witnessing (Observer, OB) of traumatic events. After observational fear training, using a 64-channel recording system, we showed that both DM and OB mice exhibited a decreased ratio of paired-pulse with intervals of 50 ms in the superficial layers of the aIC but not in the deep layers. We found that theta-burst stimulation (TBS)-induced long-term potentiation (LTP) in OB mice was significantly higher than in DM mice, and the recruitment of synaptic responses occurred only in OB mice. Compared with naive mice, OB mice showed stronger recruitment and higher amplitude in the superficial layers of the aIC. We also used low-frequency stimulation (LFS) to induce long-term depression (LTD). OB mice showed greater LTD in both the superficial and deep layers of the aIC than naive mice, but no significant difference was found between OB and DM mice. These results provide insights into the changes in synaptic plasticity in the aIC after physiological and psychological stress, and suggest that different types of stress may have different mechanisms. Furthermore, identification of the possible causes of the differences in stress could help treat stress-related disorders.